Blind signature / Musfirah Mohd Ali - Musfirah, Mohd Ali (2005)
In this thesis the author introduce a cryptographic construct called Blind Signature. This thesis is enhanced from digital signature system. The aim for this project is to develop reliable software which is capable to protect the data integrity and authenticity using blind signature method. Blind signature allow user to digitally sign the document without knowing the contents of the document. The signature has a blindness property, so if the signer later sees a document he has signed he will not be able to determine when or for whom he signed it. The organization of this report is divided into five chapters. The first chapter is about the objectives, motivations, scope and limitation of this project. Then, in order to construct the blind signature system that used an appropriate kind of method, the author did a deep research and comparison on the existing cryptography, programming languages, algorithms and systems which are explained in chapter two of this project. Beside, the author also used the software methodology model as a guidance to produce a report smoothly and on time. The chosen methodology is explained in chapter 3. In chapter 4 of this project explained the system requirements which are functional and nonfunctional requirements. This chapter also enlightened what kind of scheme that the author chose for this system. Finally, the system design is developed. In this chapter 5 the overall architecture of the system, the data flow diagram and the system interface prototype is presented.